FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMTIF PADA GENERASI Z - Taqwa, Yayang Syania Sabilla; Mukhlis, Imam (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.07.TAHUN.2022, 2022)
Consumptive behavior is behavior that arises from the existence of hedonistic consumption activities by prioritizing what is desired and not needed. The research was conducted to know the factors that influence consumptive behavior, namely lifestyle, financial literacy, demographics, and the use of e-payments. The population in the study was Generation Z in Tulungagung, which amounted to 247,439 people. While the sample was determined using an incidental sampling technique using the Slovin formula for as many as 205 samples. Collecting data in the form of a questionnaire (google form) with the method of multiple linear regression analysis models using the Ordinary Least Square (OLS) technique. Then data processing was carried out with SPSS 24. The results showed lifestyle variables (X1), demographics (X3), and the use of e-payment (X4) has a positive and significant effect on consumptive behavior. Financial literacy (X2) has no significant effect on consumptive behavior. The dominant variable in influencing consumptive behavior is X3 with a regression coefficient of 0.681, followed by X1, X4, and X2.